2007
DOI: 10.1007/s11270-007-9417-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silviculture Using Best Management Practices on Stream Macroinvertebrate Communities in Three Ecoregions of Arkansas, USA

Abstract: We examined aquatic macroinvertebrate assemblages in six Arkansas low-order streams across three ecoregions. Samples were taken at locations above and below silviculture sites using Best Management Practices (BMPs) and were compared in winter and spring for 1 year prior to logging and 2 years after treatments. Implementation at all sites scored between 89 and 100% in compliance assessments using state BMP guidelines. Deficiencies were generally limited to engineering controls designed to prevent soil erosion; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Excessive fine sediment deposition on streambeds can have detrimental effects by interfering with hydrologic exchange processes and degrading streambed quality (Schä lchli, 1992;Brunke and Gonser, 1997), altering invertebrate abundance or community composition (Angradi, 1999;Zweig and Rabeni, 2001;Kreutzweiser et al, 2005a), and reducing fish egg and fry survival by impinging on spawning and incubation substrates (Scrivener and Brownlee, 1989;Sutherland et al, 2002). Forest management guidelines and regulations in North America have attempted to mitigate logging impacts on fine sediment inputs by implementing various best management practices (Fortino et al, 2004;Vowell and Frydenborg, 2004;McCord et al, 2007). One of the more common best management practices for forestry is the application of riparian (shoreline) buffers or restricted-harvest reserves to minimize machine-generated ground disturbance and channeled flowpaths near streams and shorelines (Lee et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive fine sediment deposition on streambeds can have detrimental effects by interfering with hydrologic exchange processes and degrading streambed quality (Schä lchli, 1992;Brunke and Gonser, 1997), altering invertebrate abundance or community composition (Angradi, 1999;Zweig and Rabeni, 2001;Kreutzweiser et al, 2005a), and reducing fish egg and fry survival by impinging on spawning and incubation substrates (Scrivener and Brownlee, 1989;Sutherland et al, 2002). Forest management guidelines and regulations in North America have attempted to mitigate logging impacts on fine sediment inputs by implementing various best management practices (Fortino et al, 2004;Vowell and Frydenborg, 2004;McCord et al, 2007). One of the more common best management practices for forestry is the application of riparian (shoreline) buffers or restricted-harvest reserves to minimize machine-generated ground disturbance and channeled flowpaths near streams and shorelines (Lee et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Harvesting practices without properly implemented BMPs can negatively influence stream macroinvertebrate populations [133]; however, multiple studies in the Southeast have reported little to no change in aquatic macroinvertebrate community diversity following timber harvesting with BMPs [100,[134][135][136][137][138][139][140]. Changes in invertebrate communities, when they do occur, generally reflect a shift from allochthonous to autochthonous food resources in streams draining harvested watersheds that is relatively short-lived (<5 years) due to rapid vegetation regrowth [7].…”
Section: Macroinvertebrate Community Response To Bmpsmentioning
confidence: 99%
“…McCord et al [140] examined macroinvertebrate assemblages in six Arkansas low-order streams following harvesting with implementation of BMPs. Stream samples were collected above and below harvested tracts.…”
Section: Macroinvertebrate Community Response To Bmpsmentioning
confidence: 99%
“…The same finding was noted by Allan et al (1997) In 78 basins across the Mid-Atlantic Highlands region, Jones et al (2001) found that landscape metrics, particularly the proportion of agriculture in the catchment and forest in the riparian zone, explained 65%-84% of the variation in yields of nitrogen, phosphorus, and suspended sediments. Through the regeneration or maintenance of these ecotones, even with remnant vegetation within agricultural watersheds, it is possible to verify improvements in physical habitat structure and biotic health indices of riverine systems (Adams et al, 1995;Storey and Cowley, 1997;Lazorchak et al, 1998;Scarsbrook and Halliday, 1999;Tavzes et al, 2006;McCord et al, 2007;Theodoropoulos and Iliopoulou-Georgudaki, 2010). Since the riparian vegetation contributes to the retention of sediments and nutrients it undeniably has the ability to 26 mitigate human impacts at larger scales (Jaworski, 1993).…”
Section: Biological Condition Of Surface Watersmentioning
confidence: 99%